Drugs As Instruments: Describing and Testing a Behavioral Approach to the Study of Neuroenhancement - Brand, Ralf; Wolff, Wanja; Ziegler, Matthias (Frontiers in Psychology, 2016)
Neuroenhancement (NE) is the non-medical use of psychoactive substances to produce a subjective enhancement in psychological functioning and experience. So far empirical investigations of individuals’ motivation for NE however have been hampered by the lack of theoretical foundation. This study aimed to apply drug instrumentalization theory to user motivation for NE. We argue that NE should be defined and analyzed from a behavioral perspective rather than in terms of the characteristics of substances used for NE. In the empirical study we explored user behavior by analyzing relationships between drug options (use over-the-counter products, prescription drugs, illicit drugs) and postulated drug instrumentalization goals (e.g. improved cognitive performance, counteracting fatigue, improved social interaction). Questionnaire data from 1,438 university students were subjected to exploratory and confirmatory factor analysis to address the question of whether analysis of drug instrumentalization should be based on the assumption that users are aiming to achieve a certain goal and choose their drug accordingly or whether NE behavior is more strongly rooted in a decision to try or use a certain drug option. We used factor mixture modeling to explore whether users could be separated into qualitatively different groups defined by a shared ‘goal × drug option’ configuration. Our results indicate, first, that individuals’ decisions about NE are eventually based on personal attitude to drug options (e.g. willingness to use an over-the-counter product but not to abuse prescription drugs) rather than motivated by desire to achieve a specific goal (e.g. fighting tiredness) for which different drug options might be tried. Second, data analyses suggested two qualitatively different classes of users. Both predominantly used over-the-counter products, but ‘neuroenhancers’ might be characterized by a higher propensity to instrumentalize over-the-counter products for virtually all investigated goals whereas ‘fatigue-fighters’ might be inclined to use over-the-counter products exclusively to fight fatigue. We believe that psychological investigations like these are essential, especially for designing programs to prevent risky behavior.